Research of Axial Modification of Hoist Reducer Gear of Large Mining Mechanical Excavator - Hou Geng; Zhang Yinghui; Chen Xiuhua; Liang Jingfu; Zheng Yingmei (Jixie chuandong, 2018)
Gears in hoist reducer of large mining mechanical excavator are low speed,heavy-duty and hard surface gears. It is inevitable to occur the phenomenon of gear deviation load in mining process. Through gear axial modification,increasing gear carrying capacity and improving gear contact condition are achieved.Based on the gear slice theoretical model,mining process load spectrum of excavator is used to determine the reference load for gear axial modification of hoist reducer,the minimum gear contact stress under the reference load of modification is taken as the target of all levels pinions（ driving gears） helix angle modification,and no excessive tooth surface edge load is taken as the target of all levels pinion axial crown modification. Compare to before modification,the gear surface contact stress is obviously reduced and the edge contact condition of tooth surface is obviously improved after modification. The simulation results show that gears modification of hoist reducer of large mining mechanical excavator contribute to increase gear carrying capacity and improve the contact condition of tooth surface.